Health System Resilience in the Contex of COVID-19 Vaccination Management in Indonesia - Hermawan Saputra; Herlina J. R. Saragih; Oskar Vitriano; Nadilah Salma (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2022)
COVID-19 cases are still increasing, and some countries are even experiencing a surge in cases for the second time. COVID-19 cases in Indonesia as of April 2021 almost reached one million. The Indonesian government is targeting the COVID-19 vaccination in Indonesia to reach 70%, covering the target of vaccine recipients of around 181.5 million people. The government conveyed the target optimistically to be achieved within 15 months. However, the achievements during the initial 3 months were only 5.72% for dose I and 2.99% for dose II. This study aims to review the health system’s resilience in COVID-19 vaccination. The approaches and methods used to obtain this information were qualitative with the method of desk study, expert study, and in-depth interviews. The results showed that the components of the health resilience strategy in COVID-19 vaccination in Indonesia experienced obstacles, especially in the aspects of vaccine availability, data collection, and maximizing the role of human resources through the support of actual research on vaccine development. Thus, it is necessary to strengthen the health system that accompanies the COVID-19 vaccination program by implementing health protocols, 3T surveillance (testing-tracing-treatment), and other approaches comprehensively.